Effect of Corruption on Revenue Generation System in the Local Governments in Anambra State 2015 - 2024 - Fidelia Ifeyinwa Nzekwe Chinwuko (PT. Altaf Publishing Corp, 2026)
Corruption remains a critical impediment to effective revenue generation at the local government level in many developing countries, including Nigeria. This study empirically examines the effect of corruption on the revenue generation system of selected local governments in Anambra State from 2015 to 2024. A descriptive survey research design was adopted, and a sample of 400 respondents was derived from a projected population of 1,919,000 using the Taro Yamane sampling technique. Data were collected through structured questionnaires and analyzed using descriptive statistics and ordinary least squares (OLS) multiple regression with the aid of SPSS version 20. The findings reveal that corruption exerts a significant and negative influence on revenue generation performance in local governments, as evidenced by the regression result (t = 21.837, p < 0.001). The study further shows that corruption intensifies revenue leakages, encourages tax evasion, weakens internal control mechanisms, and hampers public service delivery. These outcomes imply that sustained fiscal instability at the grassroots level is largely driven by weak accountability and pervasive corrupt practices. The study recommends the strengthening of institutional transparency, digitalization of revenue systems, and enforcement of anti-corruption mechanisms as essential strategies for improving local government revenue performance in Anambra State.